Character Education Values in Ki Hajar Dewantara's Praxis Concept among Generation Z Students - Supriyanto, Supriyanto; Istiq’faroh, Nurul; Tri Hariastuti, Retno; Gowinda Luh Safitri, Dhian; Alfi Muhimmah, Hitta; Hadi Wibowo, Amiruddin; Windi Lukman Husyaiin, M.; Bin Hashim, Shahrin (IJORER : International Journal of Recent Educational Research, 2026)
This study examines the character education values embedded in Ki Hajar Dewantara’s educational praxis and their relevance to Generation Z students in higher education in the digital era. A mixed-methods approach with a sequential exploratory design was employed. Qualitative data were collected through in-depth interviews with students and lecturers from six study programs in the Faculty of Education, while quantitative data were obtained through questionnaires distributed to Generation Z students. Qualitative data were analyzed using NVivo through thematic coding, and quantitative data were analyzed using descriptive statistics. The findings reveal that Generation Z students internalize key character values, including leadership, discipline, social awareness, mutual cooperation, and the Trikon principles of continuity, convergence, and concentricity. Quantitative results show that 51.1% of respondents identified Ing Ngarso Sung Tulodo as the most influential value, 44.1% perceived lecturer discipline as the strongest form of role modelling, and 38% regarded collaborative group work as the primary contributor to character development. The findings indicate that lecturer exemplarity, collaborative learning environments, and the integration of local cultural values play significant roles in strengthening student character. This study contributes empirical evidence on the continued relevance of Ki Hajar Dewantara’s indigenous educational philosophy and demonstrates that character internalization among Generation Z is shaped by the interaction of role modelling, collaborative learning, cultural identity, and contextual educational experiences.